2006
DOI: 10.1111/j.1524-4725.2005.31173
|View full text |Cite
|
Sign up to set email alerts
|

Perineural Spread of Squamous Cell Carcinoma Involving the Spinal Accessory Nerve in an Immunocompromised Organ Transplant Recipient

Abstract: To our knowledge, this is the first reported case of a primary cutaneous squamous cell carcinoma of the trunk or extremity metastasizing to a cranial nerve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…Streams et al reported a case of cSCC of the shoulder presented clinical PNI of the spinal accessory nerve without spreading into the jugular foramen. 6 Schweinfurth et al 7 reported a case of metastatic conjunctival malignant melanoma presenting jugular foramen syndrome. However, no report of cSCC with PNI presented jugular foramen syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Streams et al reported a case of cSCC of the shoulder presented clinical PNI of the spinal accessory nerve without spreading into the jugular foramen. 6 Schweinfurth et al 7 reported a case of metastatic conjunctival malignant melanoma presenting jugular foramen syndrome. However, no report of cSCC with PNI presented jugular foramen syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Histologic perineural spread is asymptomatic and may be an incidental finding, because the diagnosis is made only upon microscopic examination of the cutaneous neoplasm. Clinical perineural spread is a later finding, typically occurring after more extensive neural invasion and presenting with localized symptoms of parasthesias, weakness, or pain 30,31 . Indicative of advanced disease, clinically manifest neurotropism should warrant timely, aggressive patient workup.…”
Section: Discussionmentioning
confidence: 99%
“…Skin cancers that spread to the perineural space many times express “skip” lesions throughout the nerve suggesting noncontiguous spread of the cancer along the nerves. Therefore, recurrence of these cancers is still likely after a resection with negative margins 12,14 . Patients experiencing symptoms of facial paresthesias commonly present to a neurologist.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of the patients in their study developed recurrent cancer around the primary lesion after intense treatment. Aggressive therapy, however, is encouraged for patients with perineural invasion 7,14 . Large‐field radiation therapy (75 Gy) with an altered fractionation schedule is necessary because of the propensity of perineural carcinoma to recur in not only a local but also a regional fashion 7,12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation